Degradação foto-fenton de carbono orgânico total em efluentes da indústria de beneficiamento de castanha de caju - Souza, Kátia Regina (2005)
At the cashew nut processing industry it is often the generation of wastewaters containing high content of toxic organic compounds. The presence of these compounds is due mainly to the so called liquid of the cashew nut (CNSL). CNSL, as it is commercially known in Brazil, is the liquid of the cashew nut. It looks like an oil with dark brown color, viscous and presents a high toxicity index due to the chemical composition, i.e. phenol compounds, such as anacardic acid, cardol, 2-methyl cardol and monophenol (cardanol). These compounds are bio resistant to the conventional treatments. Furthermore, the corresponding wastewaters present high content of TOC (total organic carbon). Therefore due to the high degree of toxicity it is very important to study and develop treatments of these wastewaters before discharge to the environmental. This research aims to decompose these compounds using advanced oxidative processes (AOP) based on the photo-Fenton system. The advantage of this system is the fast and non-selective oxidation promoted by the hydroxyl radicals (●OH), that is under determined conditions can totally convert the organic pollutants to CO2 and H2O. In order to evaluate the decomposition of the organic charge system samples of the real wastewater od a processing cashew nut industry were taken. This industry was located at the country of the state of Rio Grande do Norte. The experiments were carried out with a photochemical annular reactor equipped with UV (ultra violet) lamp. Based on preliminary experiments, a Doehlert experimental design was defined to optimize the concentrations of H2O2 and Fe(II) with a total of 13 runs. The experimental conditions were set to pH equal to 3 and temperature of 30°C. The power of the lamps applied was 80W, 125W and 250W. To evaluate the decomposition rate measures of the TOC were accomplished during 4 hours of experiment. According to the results, the organic removal obtained in terms of TOC was 80% minimum and 95% maximum. Furthermore, it was gotten a minimum time of 49 minutes for the removal of 30% of the initial TOC. Based on the obtained experimental results, the photo-Fenton system presents a very satisfactory performance as a complementary treatment of the wastewater studied